If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 11 = 14 Reorder the terms: 11 + -4x = 14 Solving 11 + -4x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4x = 14 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = 14 + -11 -4x = 14 + -11 Combine like terms: 14 + -11 = 3 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75
| x=16*4x | | 75=20x-15y | | 75=20x+15y | | F(x)=cos(8x-1) | | 58=17x-7y | | 58=17x+7y | | x=15-(13-19) | | x=(x+1)*(1-2x) | | x=(2x+1)*2 | | x=(12x-6)/3 | | x=7*(-x+2) | | 3/4*s=-20 | | S3/4=-20 | | x(x+8)=6x+3 | | 5x+4-3x=7x-8+11 | | y-2=1/2(x-(-4)) | | 218-178= | | 6x^3+15X^2+6x=0 | | 46.37*18.48= | | 2xy*x+3y= | | 6(x^2)+6x-44=0 | | 5(2x-6)=2(5-x) | | 3+4=-5+2 | | 3x+2=-5x+4 | | 4*(3+4x)=-18 | | 12d+7=6d+31 | | 13x+15-(x+2)= | | 5(a+7)=38 | | 47.2=9c-5 | | y=kx+10 | | 4e-7=9 | | 7p=21.7 |